Infectious Diseases of Poverty - Zhou, Xiao-Nong; Yang, Pin; Certain, Edith; Araujo-Jorge, Tania; Fu Gao, George; Oduola, Ayo MJ; Tang, Shenglan; Vega, Jeanette
Infectious Diseases of Poverty is an open access, peer-reviewed journal publishing topic areas and methods that address essential public health questions relating to infectious diseases of poverty. These include various aspects of the biology of pathogens and vectors, diagnosis and detection, treatment and case management, epidemiology and modeling, zoonotic hosts and animal reservoirs, control strategies and implementation, new technologies and application. Transdisciplinary or multisectoral effects on health systems, ecohealth, environmental management, and innovative technology are also considered. Infectious Diseases of Poverty aims to identify and assess research and information gaps that hinder progress towards new interventions for a particular public health problem in the developing world. Moreover, it provides a platform for discussion of the issues raised, in order to advance research and evidence building for improved public health interventions in poor settings.